Improved Burner Efficiency and Fuel Consumption in Domestic Cooking Appliances. (1st January 2017) - Ogedengbe, Emmanuel O. B.; Ajibade, Frank D.
ABSTRACT: The design of a preheating chamber for a safe flow of liquefied petroleum gas (LPG) or liquid fuel in a pressurized burner is investigated. In developing economies with an incessant scarcity of cooking gas, adulterated fuel is more a scarce commodity than a scary cause of fire accident to lives and household properties. Back-flow tendencies in conventional burners, associated with inevitable loss of pressure, mechanical wears, and seal leakages, are eliminated by the application of the concept of "sudden expansion, " while the fuel tends to flow back through the line at the downstream of the preheating chamber. Experimental setup of a novel feeding of liquid fuel from the overhead tank of the proposed design is compared with the performance of conventional burners. Pulsation due to back-flow tendencies of liquid fuel is calibrated for different heights ( h ) of burners, between the range of 46 mm and 60 mm. It is anticipated that the proposed design of burners will provide an effective flow of liquid fuel if uniquely characterized, using efficient treatment of the back-flow tendencies. Also, the proposed sudden expansion technology is capable of reducing the risk of an irritating exposure to adulterated fuel.